Morphokinetic analysis of pronuclei using time-lapse cinematography in bovine zygotes - Suzuki, Ryosuke; Okada, Mai; Nagai, Hiroki; Kobayashi, Junichi; Sugimura, Satoshi (Theriogenology, 2021)
The morphokinetics of pronuclei (PN) are considered crucial factors affecting embryogenesis in mammals. Whereas, since bovine zygotes contain a large number of cytosolic lipid droplets, detailed observation of PN has not been performed. In this study, we visualized PN using time-lapse cinematography (TLC) with light microscopy for the first time in delipidated bovine zygotes. The proportions of 0 PN, 1PN, 2PN, and multi-PN in delipidated bovine zygotes were 10.1%, 6.5%, 72.7%, and 10.8%, respectively. Abnormal fertilization, including 1 PN and multi-PN, was observed in 15.6% of blastocysts. The times from IVF to PN appearance, PN fading, and first cleavage in 2 PN bovine zygotes that developed into blastocysts were 10.4, 25.5, and 27.6 h, respectively, which were similar to PN morphokinetics in humans. The 2 PN zygotes showed that the prolonged time from IVF to the appearance of PN and from the fading of PN to the first cleavage negatively affected blastocyst formation. The time from appearance to fading of PN in multi-PN zygotes that developed into blastocysts was longer than that in multi-PN zygotes that did not develop into blastocysts. Besides, among zygotes that developed into blastocysts, the time from appearance to fading of PN in multi-PN zygotes was longer than that in 2 PN and 1 PN zygotes. These results suggest that PN morphokinetic abnormalities are associated with subsequent embryonic development. Observation of PN in bovine zygotes by using non-invasive visible light TLC by delipidation could be a powerful tool to clarify the relationship between PN morphokinetics and developmental competence. •Delipidation allows time-lapse imaging through light microscopy of pronuclei (PN) in bovine zygote.•PN morphokinetic abnormalities are associated with subsequent embryonic development in cattle.•Delipidation is useful for understanding the relationship between PN morphokinetics and developmental competence in cattle.